1995
DOI: 10.1123/ijsn.5.4.329
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Carbohydrate Ingestion Subsequent to Carbohydrate Supercompensation on Endurance Performance

Abstract: This investigation determined whether carbohydrate ingestion during prolonged moderate-intensity exercise enhanced endurance performance when the exercise was preceded by carbohydrate supercompensation. Seven male trained cyclists performed two trials at an initial power output corresponding to 71 ± 1 % of their peak oxygen consumption. During the trials, subjects ingested either a 6% glucose/sucrose (C) solution or an equal volume of artificially flavored and sweetened placebo (P) every 20 min throughout exer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…These results are similar to those from a cycling study conducted by Burke et al (8). However, other researchers found performance to be bettter in subjects when CHO loading and supplementation were combined before and during exercise (19), suggesting that loading and supplementation may have a synergistic effect on performance. In contrast, Widrick et al (33) found that cycling performance was significantly improved when preexercise glycogen levels were elevated by CHO loading, regardless of whether CHO was ingested throughout exercise.…”
Section: Discussionmentioning
confidence: 99%
“…These results are similar to those from a cycling study conducted by Burke et al (8). However, other researchers found performance to be bettter in subjects when CHO loading and supplementation were combined before and during exercise (19), suggesting that loading and supplementation may have a synergistic effect on performance. In contrast, Widrick et al (33) found that cycling performance was significantly improved when preexercise glycogen levels were elevated by CHO loading, regardless of whether CHO was ingested throughout exercise.…”
Section: Discussionmentioning
confidence: 99%
“…A second characteristic that may have influenced the outcome of this trial was the exercise protocol used to evaluate cycling performance. The exercise task was designed to mimic the requirements of a 100-km road cycle race (25) rather than to have subjects exercise at fixed submaximal workloads to exhaustion as in previous studies of cycling (1,6,8,20) or running (7,14,22). In other studies, CHO loading has been shown to reduce the time taken to complete a prolonged running or cycling task (21,31,32).…”
Section: Discussionmentioning
confidence: 99%
“…We have previously demonstrated that such instructional approaches were effective in helping individuals achieve target diets (Kang et al 1995).…”
Section: Subjectsmentioning
confidence: 99%